2015
DOI: 10.1038/mp.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

Rare, low frequency and common coding variants in CHRNA5 and their contribution to nicotine dependence in European and African Americans

Abstract: The common nonsynonymous variant rs16969968 in the α5 nicotinic receptor subunit gene (CHRNA5) is the strongest genetic risk factor for nicotine dependence in European Americans and contributes to risk in African Americans. To comprehensively examine whether other CHRNA5 coding variation influences nicotine dependence risk, we performed targeted sequencing on 1582 nicotine dependent cases (Fagerström Test for Nicotine Dependence score≥4) and 1238 non-dependent controls, with independent replication of common a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In 2012, a large meta-analysis in African American smokers showed a significant association between rs2036527 and self-reported CPD, but not between rs16969968 CPD [56]. However, a more recent meta-analysis showed rs16969968 is associated with increased risk for nicotine dependence in European and African Americans and provided evidence that the A allele increases risk for heavy smoking [64]. In another study, rs16969968 was not found to be consistently associated with smoking abstinence in African Americans; whereas rs2036527 was associated with active pharmacotherapy [65].…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a large meta-analysis in African American smokers showed a significant association between rs2036527 and self-reported CPD, but not between rs16969968 CPD [56]. However, a more recent meta-analysis showed rs16969968 is associated with increased risk for nicotine dependence in European and African Americans and provided evidence that the A allele increases risk for heavy smoking [64]. In another study, rs16969968 was not found to be consistently associated with smoking abstinence in African Americans; whereas rs2036527 was associated with active pharmacotherapy [65].…”
Section: Discussionmentioning
confidence: 99%
“…153 In humans, only a few specific genes have been identified with polymorphisms (alleles) that either predispose an individual to or protect an individual from drug addiction, 156 but the number is growing. For example, genome-wide association studies have implicated two acetylcholine receptors, the α4 nicotinic receptor subunit 157 and α5 nicotinic receptor subunit, 158 in the vulnerability to nicotine dependence and a single-nucleotide polymorphism associated with regulating the trafficking and gating properties of AMPA-selective glutamate receptors ( CNIH3 ) in opioid dependence. 159 …”
Section: Molecular and Genetic Treatment Targets Within Brain Circuitmentioning
confidence: 99%
“…Future studies with larger samples are needed to replicate these findings and to confirm the observed effects on individual symptoms of the DSM-IV and FTND scales. It should also be noted that the current findings are limited to common genetic variants; however, recent findings implicate a possible role for rare variants (Olfson et al , 2015, Vrieze et al , 2014), suggesting the need for future whole-genome studies incorporating common and rare polymorphisms. Readers should also consider that SAGE is a selected sample of individuals (i.e., drug addicted cases and controls).…”
Section: Discussionmentioning
confidence: 82%